เจดีย์ทรงแปดเหลี่ยมทองคำ กรุปรางค์ประธานวัดราชบูรณะ อยุธยา: การสันนิษฐานรูปแบบเต็มองค์ของเจดีย์ - ปาทา ศรินยา (วารสารศิลปกรรมบูรพา, 2021)
The golden octagonal Chedi (replica) from the main chamber of Wat Ratchaburana, Ayutthaya built in King Rama II’s reign (Chao Sam Phraya) in 1424 or around the end of the 20th century Buddhist Era. This Chedi is one of the important gold pieces that the thieves smuggled in September 1956, and the police can follow back. Originally it was enshrined on the second floor of the chamber, where gold jewelry, Royal utensils, and Royal regalia which the King brought for a Buddha offering, were found. This replica was designed to disassemble; by examination, it has been split into 5 pieces. However, this Chedi is an incomplete and unknown pattern. Comparing to the octagonal chedi found in Thailand during different periods, it is found that this golden octagonal chedi (replica) has its original prototype, starting from Rattana Chedi, Wat Chamadevi (Wat Ku Kut), Lamphun, dated back to 17 – 18 century Buddhist Era. The octagonal chedi, which was popularly built-in central and western regions of Thailand, were blended by several art styles; Lanna, Sukhothai, and Ayutthaya. Lanna Art expresses a tall shape with a pointed torus molding base, supported by Rueanthat with a facade from Sukhothai art. But did not create a channel arch to enshrine the Buddha image like architecture. The missing upper part is probably the relic chamber in the round bell shape with the spire base carries the spire, the circular tiers, and the upper part of the spire. The evolution of this kind of octagonal Chedi emerged in the 19 – 20 century Buddhist Era, obviously at Wat Kai Tia in Suphanburi, Wat Phra Kaew Sankhaburi in Chainat, Wat Tham Khao Luang in Phetchaburi including at Wat Phra Ram and Wat Chedi Sangkhlapat in Ayutthaya. The dated of this golden octagonal pagoda (replica) assumed to be in the late century 20-century Buddhist Era consistent with the time Wat Ratchaburana was built, and it was probably the wish of the king who brought the form of chedi in the early stages of the establishment of Ayutthaya to offer it as a Buddha worship.